Matrix modeling of the impact of mining and metallurgical complexes on spatial sustainable development - T. V. Serebrova (Вестник университета, 2025)
The purpose of the study is to identify a set of regional sustainability determinants in the form of the mining and metallurgical companies’ activities and the degree of their impact on the economic, social, and environmental condition of territories. Mining and metallurgical complexes contribute to meeting the needs of regional community, while creating environmental risks and natural resources exhaustion threats. To neutralize the negative impact of their activities on nature and society, Russian mining and metallurgical companies use environmental and climate strategies and follow the course for green metallurgy development using environmentally friendly and low-carbon technologies. A comprehensive study of internal and external effects of mining and metallurgical companies allowed to identify the vectors forming economic, social, and environmental sectors of regional systems. The directions and priorities of the mining and metallurgical complex activities have been identified. Their relationship with regional sustainable development has been established. The substantiated methodology based on the matrix approach allowed us to identify the leading components and drivers of territorial progress. The matrix of the impact of mining and metallurgical complexes on spatial sustainable development provides an opportunity for systemic and structural representation of all constituent components and elements with the specification of their contribution to the overall economic, social, and environmental result.